Incidence of Melanoma in Children: A Population‐Based Study in Olmsted County, Minnesota. Issue 5 (8th June 2015) - Lowe, Garrett C.; Brewer, Jerry D.; Peters, Margot S.; Davis, Dawn M. R.
Abstract Background The incidence of melanoma has been rising in the United States, with conflicting evidence regarding trends in children. Methods We identified patients 0 to 17 years old with a diagnosis of melanoma from January 1, 1970, through December 31, 2010, in Olmsted County, Minnesota. Information on survival and demographic characteristics was abstracted, and estimates of true incidence were calculated. Results The estimated true incidence of melanoma in children from 1970 to 2010 was found to be 0.62 per 100, 000 girls and 0.45 per 100, 000 boys. The incidence of melanoma in this population did not increase with time after adjusting for age and sex. Only one case of metastatic disease (lymph node) was identified. Girls were more commonly affected and the mean age of disease onset was 14 years. Five of the seven melanomas in this population arose in association with a nevus, and none involved the trunk. Overall and disease‐specific survival rates were not calculated because all patients studied were alive at the last follow‐up. Conclusion The estimated true incidence rates of pediatric melanoma from our population‐based study in Olmsted County, Minnesota, appear stable. This finding is in contrast to our prior research showing rapidly increasing incidence rates of melanoma in young and middle‐aged adults from the same population.